Pharmacologic interventions to treat renal colic pain in acute stone episodes: Systematic review and meta-analysis (2017)
Objective To assess effectiveness of pharmacologic interventions to relieve pain in patients suffering an acute stone episode. Methods Relevant trials that included patients with acute renal colic and radiological findings of urinary stones were identified in four databases. The main outcome was pain relief evaluated by Visual Analogue Scale score (VAS). Results In overall, diclofenac was superior to other NSAIDs for pain relief (MD of ?12.57 [95% CI: ?19.26, ?5.88]). Paracetamol was superior to morphine for pain reduction at 30 minutes (MD of ?3.92 [95% CI: ?6.41, ?1.43]) and also to placebo at 15 minutes (MD of ?24.77 [95% CI: ?33.19, ?16.35]) and at 30 minutes (MD of ?16 [95% CI:?29, ?2.96]) after drug administration. Finally, diclofenac was superior to paracetamol for pain reduction at 60 (MD of 6.60 [95% CI: 4.37, 8.83]) and 90 minutes (MD of 3.4 [95% CI: 2.01, 4.79]). Conclusions Diclofenac was superior to other NSAIDs and paracetamol for diminishing pain in patients suffering an acute stone episode. Paracetamol was superior to morphine and placebo for short pain relief. Future trials should address the role of paracetamol in the management of pain in patients suffering an acute stone episode. © 2017 Elsevier Masson SAS